IMPLANTED MUSCLE DERIVED STEM CELLS AMELIORATE ERECTILE DYSFUNCTION IN A RAT MODEL OF TYPE 2 DIABETES, BUT THEIR REPAIR CAPACITY IS IMPAIRED BY THEIR PRIOR EXPOSURE TO THE DIABETIC MILIEU - Kovanecz, I (J Sex Med, 2016)
INTRODUCTION: Muscle derived stem cells (MDSC) and other stem cells implanted into the penile corpora cavernosa ameliorate erectile dysfunction in type 1 diabetic (T1D) rat models by replenishing the lost corporal smooth muscle cells (SMC) and reducing fibrosis. However, no conclusive data on this question in T2/D/obesity models is available. Aim. We studied whether: a) MDSC from T2D Obese Zucker (OZ) rats at an early stage of diabetes (ED-SC), counteract corporal veno-occlusive dysfunction (CVOD) and corporal SMC loss/lipofibrosis when implanted in the OZ rats at a late stage of diabetes; b) MDSC from these late diabetes OZ rats (LD-SC) differ from ED-SC in their gene transcriptional phenotype and repair capacity. METHODS AND OUTCOMES: ED-SC and LD-SC were compared by DNA microarray assays, and ED-SC were incubated in vitro under high glucose conditions (ED-HG-SC). These three MDSC types were injected into the corpora cavernosa of late diabetes OZ rats (OZ/ED, OZ/LD, and OZ/ED-HG rats respectively). Untreated OZ (OZ/UT) and non-diabetic Lean Zucker (LZ/UT) rats were controls. Two months later, rats were subjected to cavernosometry and the penile shaft and corporal tissues were subjected to histopathology and DNA microarray assays. RESULTS: Implanted ED-SC and ED-HG-SC, improved CVOD, counteracted corporal SMC/collagen decrease and fat infiltration in long-term T2D rats, and upregulated nNOS and eNOS. LD-SC acquired an inflammatory/profibrotic/oxidative/dyslipidemic transcriptional phenotype, and failed to repair the corporal tissue. CONCLUSIONS: MDSC from pre-diabetic rats injected into the corpora cavernosa of long-term diabetic T2D rats improve CVOD and the underlying histopathology. In contrast, MDSC from long-term uncontrolled diabetic T2D rats, are imprinted by the hyperglycemic/dyslipidemic milieu with a noxious phenotype associated with an impaired tissue repair capacity. Diabetes-impacted stem cells may lack tissue repair efficacy as autografts, and should either be reprogrammed in vitro, or substituted by stem cells from allogenic non-diabetic sources.